Development of a webinar for sport coaches: Suggested best practices for supporting athletes - Poucher, Z. A.; Bissett, J. E.; Tamminen, K. A. (Journal of Sport Psychology in Action, 2021)
Coaches regularly provide social support to athletes; however, few coach education programs have addressed this topic. Therefore, this project sought to develop a social support webinar for coaches. Content was based on findings from two research studies exploring support provision to athletes. The webinar was pilot tested and then delivered online to 133 coaches. An evaluation of the webinar, consisting of surveys with an open-ended feedback section, was conducted. Results indicated increased participant capability, opportunity, motivation, and behavior for providing social support. Areas for improvement, such as providing information specific to youth and para-athletes, and enhancing participant engagement, were suggested.